Alfabetização midiática e jornalismo: práticas jornalísticas na escola para o desenvolvimento do pensamento crítico no combate à desinformação - Marquetto, Cristine Rahmeier (Universidade do Vale do Rio dos Sinos, 2021)
The present thesis looks into media literacy as a phenomenon able to qualify the audience relationship with journalistic media. Disinformation and lack of trust in the news, intensely seen after both 2016 United States and 2018 Brazilian presidential elections, are evidence of people’s inadequate preparation to deal with the load of information to which they have access and with the new content-sharing means. Journalistic speech, often still connected to positivist precepts, as well as the absence of educational background regarding the media, do not allow the public to comprehend how journalism operates and builds meanings and perceptions within society. It is assumed that media literacy may provide knowledge concerning journalistic practices and develop critical thinking, which, by their turn, are able to afford autonomy to individuals to relate with the news with further discernment and independence. At the level of journalistic practices, the tension among discursive, explanation and interpretation controls is discussed, with support of Marocco (2016, 2019), Lisboa and Benetti (2015), Meditsch (1997) and Kovach and Rosentiel (2004). Journalistic speech tied to neutrality, impartiality and objectivity, is contrasted with the ideas of Alsina (1989), Cornu (1994), and Biroli and Miguel (2017), with subjectivity being seen in this work as an important power in journalism (GENRO FILHO, 1996). In order to form a concept of media literacy, David Buckingham’s studies (2007, 2018, 2019) are used to guide theoretical understanding of the term. Besides the author, researches by Jacquinot-Delaunay et al. (2008) and Kellner and Share (2008) regarding this theme are approached. There is also differentiation of the terms “media education”, “educomunication” and “media-education”, often erroneously taken by media literacy. This thesis places itself in the inductive method of qualitative researches, more specifically in interpretative social research (ROSENTHAL, 2014). Empirical research took place in three distinct stages. In order to understand how media literacy could be systematized and implemented, a Finnish event holding a debate on this topic was attended, Finland being one of the most advanced countries in public politics for media literacy. The second and third stages correspond to participant observation in two projects which develop actions aimed at media literacy: the first one is related to Santa Catarina Federal University’s Journalistic Ethics Observatory (objETHOS), in Brazil, and the other one relates itself with Entre Les Lignes Association’s activities, in Lyon, France. The analyses from the collected data enabled the establishment of both what actions for media literacy are, and how they are done, as well as possibilities for journalism approach in schools. Moreover, it was possible to observe in these initiatives the presence of a debate on journalistic practices and the incentive to a reflexive process which contributes to the development of critical thinking. In the final remarks, some questions are raised so as to stimulate the discussion about media literacy, with arguments based on theory and observed practices. This thesis and its containing contributions may be used as a base for in-depth discussion about media literacy and its implementation in Brazil by legislators, politicians, educators, academics, teachers and interested readers.
Keywords: Alfabetização midiática; Jornalismo; Práticas jornalísticas; Pensamento crítico; Desinformação; Media literacy; Journalism; Journalistic practices; Critical thinking; Disinformation; ACCNPQ::Ciências Sociais Aplicadas::Comunicação